2019
DOI: 10.22146/rpcpe.49971
|View full text |Cite
|
Sign up to set email alerts
|

General Practitioners’ Autonomy in the Management of Non-Communicable Diseases (NCDs) in the JKN Era: Is It Feasible?

Abstract: Demographic, epidemiological, and nutritional transitions increase life expectancy, changes in lifestyles and behaviors of Indonesian people. These changes are resulting in a growing contribution of non-communicable diseases (NCDs) to morbidity and mortality, especially metabolic disorders, such as type 2 diabetes mellitus (DM), hypertension, and dyslipidemia. Approximately 10.9% of the Indonesian population above 15 years old suffers from type 2 DM (21.2 million) and 34.1% have hypertension (66.3 million) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Compared to other literature about primary care practice in Indonesia, findings in this study complement results of some studies related to GP practice under JKN implementation. 4,21,22 Findings in this study combined with results of our previous study on interviewing patients 4 complementary demonstrate a sense of adaptation and separation anxieties from both patients and GPs in primary care. Before the JKN implementation, the setting was previously regarded as a place to proceed many unnecessary referral letters to hospitals, and now, under the JKN, it has to perform more appropriate gatekeeping functions.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Compared to other literature about primary care practice in Indonesia, findings in this study complement results of some studies related to GP practice under JKN implementation. 4,21,22 Findings in this study combined with results of our previous study on interviewing patients 4 complementary demonstrate a sense of adaptation and separation anxieties from both patients and GPs in primary care. Before the JKN implementation, the setting was previously regarded as a place to proceed many unnecessary referral letters to hospitals, and now, under the JKN, it has to perform more appropriate gatekeeping functions.…”
Section: Discussionsupporting
confidence: 74%
“…Many patients still expect referrals even for mild illnesses that are manageable in primary care, while it seems that the roles of primary care are still underestimated in the health system. 9,21,22…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 However, around 20% of delivery-associated JKN reimbursement at the hospital level was for normal deliveries, 17 which translates to around US$42 million spent for services that could essentially be delivered at the primary healthcare settings. 16 Anecdotal evidence indicated that this might be due to incorrect referrals and bypassing of the referral system due to the lack of confidence of the patients in the quality of care provided at primary health facilities, [18][19][20][21][22] particularly among urban population and those from the wealthier economic background. This may be due to perceived low quality among pregnant women towards primary health facilities, 23 24 which is in line with a recent World Bank study 25 where most Indonesia PHCs have limited basic amenities and SBAs compared with secondary healthcare facilities.…”
Section: Bmj Global Healthmentioning
confidence: 99%